Kemampuan pemahaman matematis siswa SMP pada materi himpunan berdasarkan indikator restating, classifying, dan categorizing - Andi Cahya Saputra; Adi Nurjaman; Risma Amelia (IKIP Siliwangi, 2026)
This study aims to comprehensively analyze and describe the mathematical concept understanding ability of junior high school students on the topic of sets. The novelty of this research lies in the in-depth analysis of misconceptions for each indicator across all student ability levels. The method used is descriptive qualitative, involving a sample of 25 seventh-grade students at a private junior high school in Cimahi City. Data were collected through a test instrument consisting of three essay questions representing each indicator. The results showed that: (1) Students with a high ability level (16%) successfully mastered all indicators, although there were still minor inaccuracies in the classifying indicator; (2) Students with a medium ability level (76%) were only able to fulfill the restating indicator, but failed to provide logical reasoning for classifying and had not achieved the target for categorizing; (3) Students with a low ability level (8%) failed to meet the criteria across all indicators, indicating fundamental misconceptions in solving set problems. In conclusion, the mathematical understanding of the majority of students falls into the medium category, which is influenced by their lack of enthusiasm for learning.